An unexpected role of semaphorin3A/neuropilin-1 signaling in lymphatic vessel maturation and valve formation - Jurisic, Giorgia (2012)
RATIONALE: Lymphatic vasculature plays important roles in tissue fluid homeostasis maintenance and in the pathology of human diseases. Yet, the molecular mechanisms that control lymphatic vessel maturation remain largely unknown. OBJECTIVE: We analyzed the gene expression profiles of ex vivo isolated lymphatic endothelial cells to identify novel lymphatic vessel expressed genes and we investigated the role of Sema3A and neuropilin-1 (Nrp-1) in lymphatic vessel maturation and function. METHODS AND RESULTS: Lymphatic and blood vascular endothelial cells from mouse intestine were isolated using fluorescence-activated cell sorting and transcriptional profiling was performed. We found that the axonal guidance molecules Sema3A and Sema3D were highly expressed by lymphatic vessels. Importantly, we found that the semaphorin receptor Nrp-1 is expressed on the perivascular cells of the collecting lymphatic vessels. Treatment of mice in utero (E12.5-E16.5) with an antibody that blocks Sema3A binding to Nrp-1, but not with an antibody that blocks VEGF-A binding to Nrp-1, resulted in a complex phenotype of impaired lymphatic vessel function, enhanced perivascular cell coverage and abnormal lymphatic vessel and valve morphology. CONCLUSIONS: Together, these results reveal an unanticipated role of Sema3A/Nrp-1 signaling in the maturation of the lymphatic vascular network likely via regulating the perivascular cell coverage of the vessels thus affecting lymphatic vessel function and lymphatic valve development.